What determines the competitive success of young Croatian wrestlers: anthropometric indices, generic or specific fitness performance? - Škugor, K.; Gilic, B.; Karnincic, H.; Jokai, M.; Babszky, G.; Ranisavljev, M.; Štajer, V.; Roklicer, R.; Drid, P. (Journal of Functional Morphology and Kinesiology, 2023)
Identifying factors influencing wrestling performance is important for determining which capacities should be developed the most. This research aimed to investigate whether anthropometric indices, generic fitness, and specific fitness performance determine the competitive success of young wrestlers. This research included 49 Croatian Greco-Roman male wrestlers aged 17.75 ± 1.51 years. Variables included training and competing experience, anthropometric indices, generic fitness (countermovement jump and handgrip strength), and specific wrestling fitness test (SWFT). Wrestlers were separated into medallists and non-medallists (i.e., wrestlers who won a medal at the previous National Championship and wrestlers who did not win a medal, respectively). The t-test for independent samples was used to determine the differences between the two categories in all variables. Moreover, discriminant analysis was performed to identify differences in a multivariate manner. Medallists and non-medallists did not differ in anthropometric indices and wrestling experience. Medallists had better results in the countermovement jump (t = 2.55, p < 0.01), handgrip strength (t = 2.77, p < 0.01), and SWFT performance (t = 2.29, p < 0.05) than non-medallists. The discriminant analysis confirmed that performance categories differed in generic and specific fitness tests (Wilks` Lambda = 0.73, p < 0.05). It could be suggested that coaches should develop both the generic and specific fitness of their wrestlers to become more successful at competitions.